PENGEMBANGAN STANDARD OPERATING PROCEDURE (SOP) DALAM MEDIA RESERVASI PAKET WISATA CAMPING GROUND DI WISATA ALAM GUNUNG JAE LOMBOK BARAT - I.A.Y.S.D Utami Pidada; Muhamad Hendri Prayegi (Media Bina Ilmiah, 2024)
The purpose of this study is to contain broader service procedures or Standard Operating Procedures (SOP) related to tourism product reservation media, especially Camping Ground in Mount Jae natural tourism in making Camping Ground tour package reservations. West Nusa Tenggara. This research uses descriptive qualitative research methods, which are easier to collect data and deeper understanding, with the process of collecting data through interviews, observation, documentation and literature studies. Secondary data is obtained through various sources such as documentation from flyers, photos, tour packages and previous tickets related to problems in research. Primary data was obtained through structured interviews obtained from several informants, namely Pokdarwis, BUMDES, and Potential Tourists to develop Standard Operating Procedures (SOPs) on Camping Ground tour package reservation media. So that the results of this study discuss the stages of service and Standard Operating Procedure (SOP) in the Camping Ground tour package reservation media through several offline media including direct reservations, by telephone, reservations with travel agent partners, transportation companies and online media including through social media and online travel agents (OTA). This research is very important to know about the development of Standard Operating Procedure (SOP) in the reservation media of Camping Ground tour packages in the natural attractions of Mount Jae West Lombok